The state and the market economy : industrial patriotism and economic intervention in France - Hayward, Jack Ernest Shalom (Brighton, Sussex : Wheatsheaf Books ; Distributed by Harvester Press, 1986)
This is a book for those who have some familiarity with the structures of the French state and the French economy. For such readers, whether sociologists, economists of political scientists, Hayward's book will be indispensable. -- (Book Jacket)
Includes index.
Includes bibliographical references: p. 237-257.
rpm 30/08/16
Loans
Keywords: Industrial policy; France -- Economic policy -- 1945.; France